Influence of hydrodynamic characteristics of water passage elements on energy parameters of pump-turbine - Tynyanova, Irina; Rezvaya, Kseniya; Drankovskiy, Viktor (Національний технічний університет "Харківський політехнічний інститут", 2021)
Ukraine has sufficient potential for the development of renewable energy sources. Renewable energy of our country is actively developing. The demand for accumulating hydropower services will grow. This is due to the requirements of modern energy systems to align the schedule for operation in peak load zones. The solution to the problem of creating highly efficient equipment for pumped storage power plants largely depends on the correct selection of the geometry of the water passage elements of the reversible machine, which provide the required level of its energy parameters. The paper deals with the issues of modeling the hydrodynamic characteristics of the blade systems of a reversible hydraulic machine. Changes in energy parameters in the range of basic operating modes of the hill-chart are largely due to changes in the hydrodynamic characteristics of a reversible hydraulic machine. The general approach to describing the hydrodynamic characteristics of blade systems is based on the use of dimensionless parameters characterizing the flow in the characteristic section of the water passage. Expressions, which establish the relationship between the hydrodynamic characteristics and dimensionless complexes and express the general laws of the interaction of the flow with the runner of a reversible machine, are given. The influence of the hydrodynamic parameters of blade systems on the formation of the energy characteristics of a reversible hydraulic machine is considered. Analysis of the hydrodynamic characteristics of individual elements of the water passage allows to analyze their influence on the energy characteristics of a reversible hydraulic machine. The results of such an analysis are the basis for solving a wide range of issues that arise when designing a reversible hydraulic machine. This paper presents the calculations of the energy characteristics for the water passages of reversible hydraulic machines ORO200, ORO500. The calculated data indicate the decisive influence of the hydrodynamic parameters of the spatial lattice on the parameters of the optimal regime.

Україна має достатній потенціал для розвитку відновлюваних джерел енергії. Відновлювана енергетика активно розвивається, попит на гідроенергетику, що акумулюється буде зростати, це обумовлено вимогами сучасних енергосистем до вирівнювання графіка для роботи в пікових зонах навантаження. Вирішення завдання створення високоефективного обладнання для ГАЕС багато в чому залежить від правильного вибору геометрії елементів проточної частини оборотної машини, які забезпечують необхідний рівень її енергетичних показників. В роботі розглянуті питання моделювання гідродинамічних характеристик лопатевих систем оборотної гідромашини. Зміна енергетичних параметрів у діапазоні основних робочих режимів універсальної характеристики значною мірою обумовлена зміною гідродинамічних характеристик оборотної гідромашини. Загальний підхід до опису гідродинамічних характеристик лопатевих систем базується на використанні безрозмірних параметрів, що характеризують потік у характерних перетинах проточної частини. Наведено вирази, які встановлюють зв'язок гідродинамічних характеристик з безрозмірними комплексами, та виражають загальні закономірності взаємодії потоку з робочим колесом оборотної машини. Розглядається вплив гідродинамічних параметрів лопатевих систем на формування енергетичних характеристик оборотної гідромашини. Аналіз гідродинамічних характеристик окремих елементів проточної частини дозволяє проаналізувати їхній вплив на енергетичні характеристики оборотної гідромашини. Результати такого аналізу є основою для вирішення великого кола питань, що виникають під час проектування оборотної гідромашини. У цій роботі наведено розрахунки енергетичних характеристик для проточних частин оборотних гідромашин ОРО200, ОРО500. Розрахункові дані свідчать про визначний вплив гідродинамічних параметрів просторових решіток на параметри оптимального режиму.
Вплив гідродинамічних характеристик елементів проточної частини на енергетичні показники оборотних гідромашин
Keywords: reversible hydraulic machine; kinematic characteristics; energy losses; mathematical model; mode parameters; optimal mode; енергетичні характеристики; кінематичні характеристики; втрати енергії; математична модель; режимні параметри; оптимальний режим